Millennium Round and developing countries : negotiating strategies and areas of benefits - Panagariya, Arvind (UN New YorkUS, 2000)
Identifies negotiating strategies and areas of benefits from a new multilateral round of trade negotiations for developing countries. Covers areas such as trade liberalization, multilateral agreement on investment, dispute settlement, anti-dumping, and labour and environmental standards.